Potential of Mesenchymal Stem Cells (MSCs) for Various Disease Therapy: Systematic Review - Aulia, Annisa; Rismayani, Dessy; Nopiyanti, Tita; Noli, Zozy Aneloi; Maliza, Rita (Jurnal Biologi Tropis, 2024)
Mesenchymal stem cells (MSCs) are a type of multipotent stem cells that can be found in various tissues of the body, possessing good regenerative qualities and promising immunomodulatory abilities for therapy in various medical conditions. MSCs can be obtained from bone marrow, umbilical cord, adipose tissue, and Warthon's jelly. This study aims to present a systematic review of the use of mesenchymal stem cells in disease therapy, by evaluating the latest evidence regarding their efficacy and safety in various therapies. This review uses literature review methods from international data bases such as PubMed and Google Scholar. The total number of articles obtained from the database was 49 articles. These articles were then filtered using inclusion and exclusion criteria, resulting in 22 articles for this systematic review. The research findings indicate that MSCs therapy has been used for the treatment of liver fibrosis, diabetes mellitus, spinal cord injury, and COVID-19. In MSCs therapy, mechanisms involved paracrine effects (MSCs produce cytokines, growth factors, and other proteins); immunomodulation (MSCs can suppress immune cell activation, inhibit lymphocyte proliferation, modulate natural killer T cell activation, and produce anti-inflammatory factors); angiogenesis (MSCs are capable of stimulating the growth of new blood vessels through secretion of VEGF and FGF); cellular differentiation; and anti-fibrotic effects. This is what makes MSCs potentially promising as an evolving alternative treatment.